MSME Strategies in Improving the Community Economy in the Younger Generation - Tarigan, Selvida Riahta br; Sihombing, Desy Natalya (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
This research aims to identify the strategies implemented by Micro, Small and Medium Enterprises (MSMEs) in improving the economy of the younger generation. Using a qualitative research method based on literature study, analysis was carried out on various sources documenting MSME practices and strategies related to empowering the younger generation. The research results show that entrepreneurship education plays a vital role in improving the skills and innovative mentality of the younger generation, while the use of digital technology has been proven to expand markets and increase product accessibility. In addition, government policy support and financial access, such as tax incentives and microfinancing, are crucial in creating a conducive environment for the growth of MSMEs and the active participation of the younger generation. This research concludes that collaboration between MSMEs, the government and the younger generation can strengthen the local economy and reduce unemployment among youth.